Integrating two models of Multi - Criteria ABC Inventory Classification - abdolhamid safaai ghadikolai; mehrdad madhushi; mansur esmail zadeh (مطالعات مدیریت بهبود و تحول, 2008)
Faced with the heavy burden of dealing with a large number of items, companies must classify the items in inventory and develop effective inventory control policies for these classes. Inventory classification using ABC analysis is one of the most widely employed techniques in organizations. The purpose of ABC classification is highlights the need for further study on effective factors in knowledge management processes. In the present age of ideas with the specification of uncertainty, knowledge management counts for an effective tool in the application of human capital and accountability to strategic uncertainties. In this direction, effective knowledge management initiatives need a culture that values sharing knowledge among individuals as well as the creation and application of it. On the other hand, much of the literature emphasizes the fundamental role of managers and leaders in shaping an appropriate culture that facilitates knowledge management processes. Hence, in this article, the value perspective (Denison and Quinn) and the behavioral perspective of organizational culture, and transformational, transactional and laissez- faire leadership styles also their role in developing four key knowledge management activities ( creation, storage, transfer and application) will be analyzed. As part of this analysis, a set of hypothesizes will be provided in order to explain the organizational culture fostering each of knowledge management processes also the compatible leadership style for developing and shaping the underlying culture. Finally the article concludes by considering fruitful areas for further research.